قاعدة الضرورة تقدر بقدرها وتطبيقاتها في النوازل الطبية المعاصرة التداوي بالمحرمات أنموذجا - غمام عمارة, خديجة (University of Eloued جامعة الوادي, 2018)
"الملخص تعالج هذه المذكرة قاعدة من القواعد الفقهية المتمثلة في قاعدة الضرورة تقدر بقدرها، فهي قاعدة تحل مع الضرورة حيث حلت- ذلك أنها حاكمة لما يستباح من المحضور حال الضرورة مقدارا وزمنا، ولها في مجال العلوم الطبية، أهمية كبرى، ومكانة عظمى، في بيان الضوابط الشرعية التي يجب على الطبيب والمريض عدم مجاوزتها أثناء العلاج بالمحرمات. وقد حاولت الدراسة الإجابة على الاشكال الرئيسي التالي: ماهي أهم الضوابط الشرعية لقاعدة"" الضرورة تقدر بقدرها "" في مسائل التداوي بالمحرمات؟. وقد قسمت الدراسة إلى مبحثين: فالمبحث الأول تضمن بيان ماهية قاعدة"" الضرورة تقدر بقدرها"" أما الثاني فقد تناول تطبيقات القاعدة على المسائل الطبية المتعلقة بالتداوي بالمحرمات، وذلك بدراسة أربع مسائل: أولها ترقيع جلد الآدمي بجلد الحيوان النجس، ثم التداوي بنقل الدم من آدمي لآخر، ثم تليها التداوي بالسموم والتداوي بالمخدرات وختمت المذكرة بخاتمة تضنمت أهم النتائج والتوصيات المتوصل إليها " "Summary This memorandum deals with a rule of jurisprudence that is based on the necessity rule. It is a rule that is solved with necessity where it has been resolved. It is the ruling for what is not permissible from the presence of necessity when it is necessary and it is necessary for it in the field of medical sciences. Which the doctor and the patient must not exceed during treatment with taboos. The study tried to answer the following main forms: What are the most important rules of legitimacy for the rule of ""necessity estimated in its capacity"" in the treatment of taboo? The second study dealt with the applications of al-Qaeda on the medical issues related to the treatment of taboo, by studying four issues: the first is the patching of the human skin with the skin of the unclean animal, then the treatment of transfusion of blood from one person to another , Followed by medication with toxins and drug treatment and concluded the memorandum concluded with the most important findings and recommendations reached "
مذكرة ماستر تخصص فقه وأصول
Keywords: القواعد الفقهية - التداوي بالمحرمات - النوازل الطبية; Principles of Jurisprudence - Treatment of taboos - Medical insults